Quality of life in congenital diaphragmatic hernia survivors treated at a non-ECMO centre from 1998 to 2015: a cross-sectional study - Palle Toft; Anne Maria Herskind; Ulla Lei Larsen; Steven Aagaard Christensen; Thomas Strøm; Susanne Halken (BMJ Publishing Group, 2024)
Background Survival of infants with congenital diaphragmatic hernia (CDH) has increased and more insight is warranted on the long-term issues of this condition.Methods We conducted a cross-sectional study on consecutively born infants with CDH treated at a non-extracorporeal membrane oxygenation centre (ECMO) from 1998 to 2015. Quality of life was evaluated using the Pediatric Quality of Life Inventory Generic Core Scale 4.0 (PedsQL(4.0)) Questionnaire and an interview was conducted to assess for CDH-related morbidity.Results 71 eligible CDH survivors were identified and 51 consented to participate: aged 5-21 years, 28 (54.9%) male, 42 (82.4%) with left-sided hernias, 10 (19.6%) needed patch repair, median length of stay in hospital was 27.96 days (IQR 18.54-61.56). Forty-nine completed the questionnaire with a median PedsQL total score for participants of 82.6 vs 83.7 of the total proxy parent score (p=0.04). Total score was significantly lower for participants aged 5-12 years compared with participants aged 13-21 years (p=0.04); however, when reported by domains, only the physical score remained significantly lower (p=0.048). Two (4.1%) participants' and 8 (16.7%) proxy parents' scores were below 70 and considered at risk of impaired quality of life. We identified the presence of CDH-related morbidity in our population, and confirmed an association between respiratory morbidity and lower PedsQL scores (p=0.04).Conclusion We report an overall good quality of life in our population with CDH. However, a lower physical score was noted when compared with a national Danish cohort and individuals at risk of reduced quality of life were recognised. Structured follow-up programmes to identify and ensure early management of CDH-related issues may prevent a negative impact on quality of life.